2002
DOI: 10.1902/jop.2002.73.7.748
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor and Transforming Growth Factor‐α and ‐β1 Are Released From Human Cultured Gingival Epithelial Sheets

Abstract: This study indicates that meaningful amounts of VEGF and TGF-alpha and -beta1 are released from HCGES, which suggests potential for promoting wound healing and tissue regeneration after grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…93 Several studies have indicated that TGF-b is able to induce keratinocytes to produce VEGF gene expression. 59,97 Tian et al 93 found that TGF-b increased and reached a peak on day 3 in the silver nanoparticle-treated animals and may explain why significantly higher VEGF mRNA levels were maintained in the early stage of wound healing. 93 Tian et al 93 concluded that silver nanoparticles can modulate local and systemic inflammatory response following burn injury by cytokine modulation (Table 3).…”
Section: Silver Nanoparticles Suppress Both Local and Systemic Inflammentioning
confidence: 98%
“…93 Several studies have indicated that TGF-b is able to induce keratinocytes to produce VEGF gene expression. 59,97 Tian et al 93 found that TGF-b increased and reached a peak on day 3 in the silver nanoparticle-treated animals and may explain why significantly higher VEGF mRNA levels were maintained in the early stage of wound healing. 93 Tian et al 93 concluded that silver nanoparticles can modulate local and systemic inflammatory response following burn injury by cytokine modulation (Table 3).…”
Section: Silver Nanoparticles Suppress Both Local and Systemic Inflammentioning
confidence: 98%
“…It consists in the formation of new capillaries due to the budding of endothelial cells [19][20][21][22][23][24][25][26][27]. This process involves epithelial cell division, selective degradation of vascular basement membranes and endothelial cell migration [19][20][21][22][23][24][25][26][27]. Inflamed tissues tend to increase the inflammatory mediators expression, which in turn may promote angiogenesis [25].…”
Section: Introductionmentioning
confidence: 99%
“…Inflamed tissues tend to increase the inflammatory mediators expression, which in turn may promote angiogenesis [25]. One of the major angiogenic activators is vascular endothelial growth factor (VEGF), which has been detected in vascular endothelial cells, inflammatory cells, junctional, sulcular and gingival epithelium during reparative processes [22,26]. Further factors of critical importance in the inflammation process are Ki-67 and nitric oxide synthases (NOS).…”
Section: Introductionmentioning
confidence: 99%
“…Its role in the development, progression, or healing of periodontal lesions has not been elucidated yet 17‐25 . In periodontal tissues, angiogenesis seems to be important both for the maintenance of tissue health and in chronic inflammatory periodontal diseases 17,19‐23 . Inflamed tissues seem to enhance the expression of inflammatory mediators, which in turn may promote angiogenesis 17 .…”
mentioning
confidence: 99%